Infographics. Football-specific strategies to reduce COVID-19 transmission - Carmody, S.; Ahmad, I.; Gouttebarge, V.; Malhotra, A.; Glover, D.; Massey, A. (British Journal of Sports Medicine, 2020)
Football stakeholders have been advised to exercise caution when determining when to reintroduce professional football due to the risks of COVID-19 overburdening health services and also concerns regarding potential negative health sequelae for players who contract the disease. There are considerable economic, social and wider incentives attached to resuming professional football. Should this occur prematurely it would present significant ethical and medical challenges to medical teams. Robust risk assessment and mitigation procedures would facilitate professional football to return in some format despite the ongoing pandemic, but they will not eliminate risk completely. This article considers the evolving science pertinent to professional footballers in the context of COVID-19, with the overarching purpose to ensure the health and safety of players, staff, their families and the general public. The primary focus of this article is on strategies to reduce the risk of human-to-human transmission during football activity, aspects of which will be relevant to other sports.